Corrosive disadvantage: the impact of fracking on young people's capabilities. Issue 5 (3rd September 2021) - Dunlop, Lynda; Atkinson, Lucy; Turkenburg-van Diepen, Maria
ABSTRACT: Hydraulic fracturing ('fracking') is a policy problem that is both a spatial and temporal issue, touching on economic, environmental, health, safety, political and social concerns of interest to youth. This empirical study focuses on the impact of fracking on youth in communities in England. The Capabilities Approach is used as a lens for understanding the experiences of young people in their late teens. The article draws on focus groups with young people which took place within a 20-mile radius of exploratory fracking sites. The study contributes to the understanding of youth experience of controversial energy interventions. Findings suggest that fracking prevents young people from living the lives they have reason to value, and has, and will continue to have, a negative impact on wellbeing in the present and in the future. Fracking creates conditions of corrosive disadvantage for affected youth. Greater inclusion of youth perspectives in environmental decision-making is needed.